A Comparison of The Justice System for Child Cyberbullying Offenders in Indonesian and South Korean Criminal Law - Citra Anggun Puspita (JURNAL ILMIAH LIVING LAW, 2025)
This study aims to determine the minimum age at which a child can be sanctioned in the legal context of Indonesia and South Korea, as well as to evaluate legal justice measures for children involved in cyberbullying cases in the criminal legal systems of the two countries. The research conducted is normative and descriptive. The approach applied includes legal methods, comparison, and a conceptual approach. This research compares Law No. 11/2012 on the Juvenile Justice System in Indonesia with the Criminal Code of the Republic of Korea in relation to the Juvenile Act 1958. This research analyzes the age limit of children who can be punished for cyberbullying behavior in the context of Indonesian and South Korean law. The technique for collecting legal data is carried out through literature studies complemented by juridical analysis, in accordance with the characteristics of normative legal research. The results of the research and analysis show that regulations relating to cyberbullying, especially in the context of the criminal justice system for children, in Indonesia and South Korea, seek to protect children's rights, including the rights of children who commit cyberbullying. Strict measures in law enforcement are not ignored in order to create a deterrent effect for children. It is important to understand the reasons behind the criminal behavior of these children as part of the legal considerations relevant to the individuals concerned.